2015
DOI: 10.5430/jct.v4n1p83
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Achievement Motivation and Academic and Social Self-concept in Gifted Students of Higher Education

Abstract: The purpose of this study is to identify groups of gifted university students that differ in their self-concept and achievement motivation. For this, 80 students who achieved scores of the 95th percentile or higher in the Raven's Progressive Matrices test were selected. Two groups were identified in terms of their social self-concept and the competitiveness-oriented achievement motivation variables. The first group (Protected) gathered 51 (63.7%) gifted students who exhibited high levels of social self-concept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
2
4
0
Order By: Relevance
“…They do not differ in any of the used tools. These results support research that points out that the students with high abilities differentiate in cognitive aspects, which is obvious, but not in their personal and social adjustment (Borges et al, 2011), neither in their emotional reaction (Valadez et al, 2015;Egeland, 2019;França-Freitas et al, 2019).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…They do not differ in any of the used tools. These results support research that points out that the students with high abilities differentiate in cognitive aspects, which is obvious, but not in their personal and social adjustment (Borges et al, 2011), neither in their emotional reaction (Valadez et al, 2015;Egeland, 2019;França-Freitas et al, 2019).…”
Section: Discussionsupporting
confidence: 88%
“…Some authors report that these children can show feelings like anxiety and depression due to their high sensibility (Silverman, 1993;Wellisch and Brown, 2012;Karpinsky et al, 2018;Armstrong et al, 2019). However, others point to the opposite, indicating that they have a good socio-emotional fit (Valadez et al, 2015;Egeland, 2019;França-Freitas et al, 2019). Meanwhile, Borges et al (2011) say that cognitive abilities can be used to solve any problems, allowing them a similar adjustment to their fellow partners.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, with regard to physical wellbeing, the high-ability students do not show worse stability than the community samples in these conditions of uncertainty that have resulted from being kept at home due to the confinement caused by the health alert, thus confirming the results found in other studies and under pre-pandemic conditions (Zeidner and Shani-Zinovich, 2011;Olivier et al, 2016). This result also helps to dispel the myth that they establish worse relationships with their peers, and, in general, confirms that no specific problems in personal adjustment or in socio-emotional areas have to be expected in that sample (Borges et al, 2011;Valadez et al, 2015;Egeland, 2019).…”
Section: Discussionsupporting
confidence: 86%
“…Stereotypes regarding lesser personal adjustment (Preckel et al, 2015;Baudson and Preckel, 2016;Matheis et al, 2017) have been shown to be false (Reis and Renzulli, 2004;Borges et al, 2011;Bacal, 2015;Valadez et al, 2015;Egeland, 2019;França-Freitas et al, 2019), or those relating to their satisfaction with life (Bergold et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This finding can be justified with contributions which state that there are many good students that tend to be individualist (Silverman 1990;Valadez Sierra et al 2015).…”
Section: Rq2: Effect Of Forum-related Variables In Predictionmentioning
confidence: 97%